Integrative Taxonomy Reveals Molicola uncinatus and Gymnorhynchus gigas (Cestoda: Trypanorhyncha) Coinfection in the Atlantic Pomfret Brama brama From the Mediterranean Sea, With Notes on the Phylogenetic Position of G. gigas Within the Family Gymnorhynchidae - Santoro, Mario; Palomba, Marialetizia; Aco Alburqueque, Renato; Mattiucci, Simonetta (Frontiers in Veterinary Science, 2022)
The cestode family Gymnorhynchidae Dollfus, 1935 (order Trypanorhyncha) comprises three genera and six valid species that are typically intestinal parasites of large pelagic sharks. Members of Gymnorhynchidae show a wide geographic distribution and represent a global sanitary concern because as larvae they infect the edible flesh of several commercially important fishes with some species having allergenic potential. Larval Gymnorhynchidae collected from the muscles of the Atlantic pomfret Brama brama from various localities in the Mediterranean Sea were identified and characterised by combining traditional morphology, SEM, and molecular analyses using newly generated nuclear 18S and 28S rRNA sequences. Overall, 98 larvae were collected from 20 (100%) of the Atlantic pomfret (intensity of infection: 4.9; range: 1-12). High quality sequences were obtained for 54 larvae. Of these, 11 and 43 larvae were identified as Molicola uncinatus and Gymnorhynchus gigas, respectively. Phylogenetic analyses showed within Gymnorhynchidae the existence of three main clades. The first, included species of G. gigas and M. uncinatus from the Mediterranean and Atlantic; the second and third major clades, included an unidentified species of Molicola from the Indian Ocean and specimens of G. isuri from the Mediterranean and Atlantic, respectively. Finally, Chimaerarhynchus rougetae was the basal and most diverging taxon in all the elaborations from the two different data sets. Phylogenetic analysis suggested that G. gigas is more closely related to members of Molicola. We demonstrated the coinfection of M. uncinatus and G. gigas from all localities studied and extended the intermediate host and geographical range of M. uncinatus by including the Atlantic pomfret and the Tyrrhenian and Ionian Seas, respectively. The present results supported the previous proposal that G. gigas and Molicola species should be included in the same genus. Our study demonstrated the usefulness of the integrative taxonomy for the unequivocal recognition of larval trypanorhynch species and to resolve the current difficulties in the taxonomy and to elucidate the poorly known ecological and biological aspects of members of Gymnorhynchidae.